Graphene/V2O5 Cryogel Composite As a High‐Energy Cathode Material For Lithium‐Ion Batteries. Issue 3 (27th January 2017) - Maroni, Fabio; Birrozzi, Agnese; Carbonari, Gilberto; Croce, Fausto; Tossici, Roberto; Passerini, Stefano; Nobili, Francesco
Abstract: This work reports the synthesis and characterization of an amorphous V2 O5 cryogel/graphene nanosheet composite as a high‐performance cathode material. The optimization of electrode processing is conducted by using the environmentally friendly poly acrylic acid as the binder and ethanol as the solvent. The nanocomposite material shows outstanding capacity values, exceeding 300 mAhg −1 reversible capacity upon galvanostatic cycling tests at 280 mAg −1 (C/2 charge/discharge rate), and more than 100 mAhg −1 at 5600 mAg −1 (10C). A subsequent electrochemical impedance spectroscopy study gives useful insights into the cathode/electrolyte interface. Abstract : High–energy nanocomposite cathode : Owing to a straightforward synthesis process and an optimized and sustainable electrode‐processing procedure, it is possible to prepare a high‐energy amorphous V2 O5 /graphene nanocomposite cathode material able to deliver a specific capacity of over 300 mAhg −1 during galvanostatic cycling tests.